Restoration-Guided Implant Rehabilitation of the Complex Partial Edentulism: a Clinical Report - Nikitas Sykaras; Fotios Tzerbos; Vasilios Tzoras (Stilus Optimus, 2010)
Background: The hard and soft tissue deficiency is a limiting factor for the prosthetic restoration and any surgical attempt to correct the anatomic foundation needs to be precisely executed for optimal results. The purpose of this paper is to describe the clinical steps that are needed to confirm the treatment plan and allow its proper execution.Methods: Team work and basic principles are emphasized in a step-by-step description of clinical methods and techniques. This clinical report describes the interdisciplinary approach in the rehabilitation of a partially edentulous patient. The importance of the transitional restoration which sets the guidelines for the proper execution of the treatment plan is especially emphasized along with all the steps that have to be followed.Results: The clinical report describes the diagnostic arrangement of teeth, the ridge augmentation based on the diagnostic evaluation of the removable prosthesis, the implant placement with a surgical guide in the form of the removable partial denture duplicate and finally the special 2-piece design of the final fixed prosthesis.Conclusions: Clinical approach and prosthesis design described above offers a predictable way to restore partial edentulism with a fixed yet retrievable prosthesis, restoring soft tissue and teeth and avoiding an implant supported overdenture.